Evaluation of A.E. Kulakovsky’s writing during the nascent period of Yakutsk literary criticism - Darbasova, Svetlana (Revista EntreLinguas, 2021)
The research presents a study on the issue of evaluating the criticism of A.E. Kulakovsky (1877-1926), the Yakut literature founder, at the stage of Yakut literature formation. Criticism, from the first critic reviews to contemporary monographs, reflect the entire path of the Yakut literary criticism development. In the 1920s, young criticism took a difficult path of transition from literature to field of political struggle. The cultural, historical, and sociopolitical situation in the country resulted in opposite opinions of critics and writers, from that period, about classics works of the Yakut literature. The study is grounded on the synaestheticism principle. The results of the study consist in the analysis and systematization of the first critical comments, reviews, and articles and previously unrevealed materials from periodicals of this time, which allows identifying the peculiarities of the perception of the first poet’s creative heritage by critics and writers of the emerging Yakut literature. La investigación presenta el estudio del tema de la evaluación de la crítica de A.E. Kulakovsky (1877-1926), el fundador de la literatura Yakut, en la etapa de formación de la literatura Yakut. La crítica, desde las primeras reseñas críticas hasta las monografías contemporáneas, refleja todo el camino del desarrollo de la crítica literaria Yakut. En la década de 1920, la crítica joven tomó un difícil camino de transición de la literatura al campo de la lucha política. La situación cultural, histórica y sociopolítica del país generó opiniones opuestas de críticos y escritores de ese período sobre la obra de los clásicos de la literatura de Yakut. El estudio se basa en el principio de sinestesismo. Los resultados del estudio consisten en el análisis y sistematización de los primeros comentarios críticos, reseñas y artículos y materiales inéditos de publicaciones periódicas de este período, lo que permite identificar las peculiaridades de la percepción de la herencia creativa del primer poeta por parte de críticos ...